Neural Connectivity Changes Facilitated by Familiar Auditory Sensory Training in Disordered Consciousness: A TBI Pilot Study - Bender Pape, Theresa L.; Livengood, Sherri L.; Kletzel, Sandra L.; Blabas, Brett; Guernon, Ann; Bhaumik, Dulal K.; Bhaumik, Runa; Mallinson, Trudy; Weaver, Jennifer A.; Higgins, James P.; Wang, Xue; Herrold, Amy A.; et al. (Frontiers in Neurology, 2020)
For people with disordered consciousness (DoC) after traumatic brain injury (TBI), relationships between treatment induced changes in neural connectivity and neurobehavioral recovery have not been explored. To begin building a body of evidence regarding the unique contributions of treatments to changes in neural network connectivity relative to neurobehavioral recovery, we conducted a pilot study to identify relationships meriting additional examination in future research. To address this objective, we examined previously unpublished neural connectivity data derived from a randomized clinical trial (RCT). We leveraged this data because treatment efficacy, in the RCT, was based on a comparison of a placebo-control with a specific intervention, the familiar auditory sensory training (FAST) intervention consisting of autobiographical auditory-linguistic stimuli. For this pilot study, we selected a sub-group of RCT participants with high quality imaging data (FAST n=4 and Placebo n=4) to examine treatment related changes in brain network connectivity and how and if these changes relate to neurobehavioral recovery. To discover promising relationships among the FAST intervention, changes in neural connectivity and neurobehavioral recovery, we examined 26 brain regions and 19 white matter tracts associated with default mode, salience, attention, and language networks as well as three neurobehavioral measures. Of the relationships discovered, the systematic filtering process yielded evidence sup-porting further investigation of the relationship among the FAST intervention, connectivity of the left inferior longitudinal fasciculus and auditory-language skills. Evidence also suggests that future mechanistic research should focus on examining the possibility that the FAST supports connectivity changes by facilitating re-distribution of brain resources. For a patient population with limited treatment options, the reported findings suggest that a simple, yet targeted, passive sensory stimulation treatment may have altered functional and structural connectivity. If replicated in future research, then these findings provide the foundation for characterizing the unique contributions of the FAST intervention and could inform development of new treatment strategies. For persons with severely damaged brain networks, this report represents a first step toward advancing understanding of the unique contributions of treatments to changing brain network connectivity and how these changes relate to recovery of persons with DoC after TBI.